Public acceptence towards BMX racing sport / Azhar Zulkiflee - Zulkiflee, Azhar (2014)
BMX stands for bicycle motocross. Riders use BMX bikes in races and to perform stunts. BMX bikes are smaller than most bikes. They have wide tires that are designed to ride over the ground. BMX racing bikes are shaped like motorcycle. The bikes have small, low frames. The frames are lightweight and strong. Riders of all ages can enjoy BMX racing. Most people ride them just for fun, and it still can be accepted especially·among the teenagers. Some riders join organized races and other competitions. In this paper, the researcher, want to study the level of public acceptance towards BMX Racing. By using random sample of respondent choose among the public area Bandar Hilir, Melaka, the researcher intend to determine the factor based on the independent variable, level of knowledge, level of income, and advertisement. This research will help the organizer of BMX Racing to improve and develop through the tournament. It is very important to make sure that people aware about the existence of the racing tournament and support this kind of sport.